Auger electron wave packet interferometry on extreme timescales with coherent soft x-rays. (25th November 2020) - Usenko, Sergey; Schwickert, David; Przystawik, Andreas; Baev, Karolin; Baev, Ivan; Braune, Markus; Bocklage, Lars; Czwalinna, Marie Kristin; Deinert, Sascha; Düsterer, Stefan; Hans, Andreas; Hartmann, Gregor; et al.
Abstract: Wave packet interferometry provides benchmark information on light-induced electronic quantum states by monitoring their relative amplitudes and phases during coherent excitation, propagation, and decay. The relative phase control of soft x-ray pulse replicas on the single-digit attosecond timescale achieved in our experiments makes this method a powerful tool to probe ultrafast quantum phenomena such as the excitation of Auger shake-up states with sub-cycle precision. In this contribution we present first results obtained for different Auger decay channels upon generating L-shell vacancies in argon atoms using Michelson-type all-reflective interferometric autocorrelation at a central free-electron laser photon energy of 274.7 eV.